Exploring the Use of Oral Narrative Composition to Enhance Students Speaking Skill in EFL Beginners Classes: A Case Study of Some Secondary Schools in Benin. - TEBA, Sourou Corneille (My University, 2019)
The aims of this paper are: firstly to know if using oral narrative composition has an impact on teaching and learning English as a foreign language, secondly to describe how oral narrative composition gives an influence on speaking skill of EFL beginners’ classes in Benin. The methodology adopted during the investigation of this paper consists in collecting information from EFL teachers and learners through the means of classroom observation, interviews and questionnaires distributed to them to gather reliable data. The questionnaires were analyzed in terms of frequency and percentages by means of statistical packages. From the results the majority of EFL teachers do not make use of oral narrative composition as it must be to teach speaking skill in EFL beginners’ classes. Positive improvement on students’ active participation, confidence and fluency in speaking skill can be realized through the well implementation of oral narrative composition. Using it in the process of teaching and learning creates good and enjoyable circumstances, reduces the boredom and stress of learners.
Keywords: Oral; Narration; Composition; Stress; Boredom